Consumers’ valuation of academic and deprivation-compensating aspects of school performance in England - Andreou, Sofia N. (My University, 2018)
Purpose – The purpose of this paper is to investigate the willingness of households to pay for academic and deprivation-compensating components of the Contextual Value Added (CVA) indicator of school quality used in England in order to locate themselves in the catchment area of state schools. Deprivation-compensating school performance, defined as the difference in the disadvantaged intake between two schools with the same academic performance. Design/methodology/approach – The empirical analysis, based on data drawn from three independent UK data sources, used parametric and non-parametric analysis approaches. The analysis conducted separately for primary and secondary schools, because household behaviour can differ between these two levels of education. Findings – Consumers are willing to pay for houses in the catchment area of primary and secondary schools with high academic achievement, as measured by the mean score; whereas, the component of the CVA indicating deprivation-compensating aspects of school performance is found to have a positive effect only on the price of houses in the catchment area of primary schools in London; its impact on the price of houses elsewhere is mostly negative. Practical implications – The analysis in this study suggested that the recently adopted practice of using CVA as a measure of school quality in England can encourage government and Local Authorities to pay more attention to raising the deprivation-compensating aspects of school performance of their schools. Originality/value – This is the first study to explore the value which households attach to deprivation-compensating outcomes, at a given level of academic performance using the CVA indicator.
Keywords: House prices; Education equality; Consumer valuation; School performance; Hedonic analysis; Contextual value added; D12; I21